Analysis of dispersion characteristics in helically corrugated coaxial waveguides: a theoretical and comparative study - Ying Xin Lai; An Yan; Cheng Chen; Wei Chao Kuang; Shan Jin Wang (New Journal of Physics)
Helically corrugated waveguides are valuable for constructing high-performance gyrotron devices and high-power pulse compressors. This paper establishes a theoretical model to analyze the dispersion characteristics of helically corrugated coaxial waveguides, where the dispersion equations for solving the propagation constants of coupled eigenmodes, as well as the detailed coupling coefficients for various mode combinations are provided. On this foundation, the dispersion characteristics of corrugated coaxial waveguides featuring single and dual helical surfaces were systematically analyzed and compared with those of helically corrugated cylindrical waveguides in the context of pulse compression application. The findings reveal that helically corrugated coaxial waveguides operating in TEM mode require fewer auxiliary components, exhibit a wider frequency range of monotonically decreasing group velocity, and have a larger dynamic range of group velocity changes; notably, the dispersion performance of the waveguides with dual corrugated conductors can even be manipulated by varying the initial phase difference between the inner and outer helical corrugations. These advantages contribute to a reduction in compressor’s length, an increase in compression ratio and energy efficiency, and an enhancement in applicability.